2014
DOI: 10.1177/1363461514536358
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Historical Trauma

Abstract: Recent years have seen the rise of historical trauma as a construct to describe the impact of colonization, cultural suppression, and historical oppression of Indigenous peoples in North America (e.g., Native Americans in the United States, Aboriginal peoples in Canada). The discourses of psychiatry and psychology contribute to the conflation of disparate forms of violence by emphasizing presumptively universal aspects of trauma response. Many proponents of this construct have made explicit analogies to the Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
322
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(340 citation statements)
references
References 48 publications
3
322
0
15
Order By: Relevance
“…It is commonly believed that inferior mental health conditions among indigenous people may be due to historical injustice and oppression [50]. Our finding of a higher prevalence of PTS symptoms among the Sami than among the non-Sami may reflect more trauma exposure among the Sami compared to the majority population [11,56]. To our knowledge, no studies on PTSD diagnosis or PTS among indigenous Sami have previously been performed.…”
Section: Discussionmentioning
confidence: 65%
“…It is commonly believed that inferior mental health conditions among indigenous people may be due to historical injustice and oppression [50]. Our finding of a higher prevalence of PTS symptoms among the Sami than among the non-Sami may reflect more trauma exposure among the Sami compared to the majority population [11,56]. To our knowledge, no studies on PTSD diagnosis or PTS among indigenous Sami have previously been performed.…”
Section: Discussionmentioning
confidence: 65%
“…Among Indigenous peoples, intergenerational trauma, as an effect of "shared recognition" is often linked to the innumerable deaths of many peoples through violence, mass genocide, and the spread of disease (Kirmayer et al, 2014). Intergenerational trauma is also related to the impact of loss in connection to the loss many Indigenous people endure of their homes, lands and for some generations their culture (Dudgeon & Kelly, 2014;Ranzijn, McConnochie & Nolan, 2009).…”
Section: Trauma and Indigenous People: Shared Recognitionmentioning
confidence: 99%
“…For example, recent epidemiological research exploring the relationship between Indigenous people's health conditions and colonialism uses "residential school attendance" and "removal from biological parent" as the primary indicators of colonial violence and trauma (see for instance Cedar Project et al, 2008;Lemstra, Rogers, Thompson, Moraros, & Buckingham, 2012;Mehrabadi et al, 2008;Spittal et al, 2007). While these indicators are important, given their intergenerational effects, it is equally important to recognize that there is an extensive system of colonial policies, practices, and discourses influencing Indigenous people's lives and their profound material and social impacts (Kirmayer et al, 2014;Maxwell, 2014;Tait, 2009). For instance, Maxwell (2014) revealed that mental health and child development discourses often discursively mobilize historical trauma to justify state-sanctioned interventions into Indigenous families "on the grounds of children's needs for 'protection' and parents' needs for clinical intervention" (p. 426).…”
Section: Lived Histories: Colonial Child Welfare Policies and Practicmentioning
confidence: 99%